2014
DOI: 10.3390/molecules190710427
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Analysis of Rhizoma Smilacis glabrae by Ultra High Performance Liquid Chromatography Coupled with LTQ OrbitrapXL Hybrid Mass Spectrometry

Abstract: Rhizoma Smilacis glabrae, a traditional Chinese medicine (TCM) as well as a functional food, has been commonly used for detoxification treatments, relieving dampness and as a diuretic. In order to quickly define the chemical profiles and control the quality of Smilacis glabrae, ultra high performance liquid chromatography coupled with electrospray ionization hybrid linear trap quadrupole orbitrap mass spectrometry (UHPLC-ESI/LTQOrbitrap-MS) was applied for simultaneous identification and quantification of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 9 publications
3
27
0
Order By: Relevance
“…Note that the presence of phragmalintype limonoids in the BM extracts has been indicated by ESI(+)-MS analysis 27 and by other classical phytochemical approaches. Note that this molecule has also been reported in other types of tree woods such as Phyllocladus trichomanoides, 40 Rhizoma Smilacis glabrae 41 and Trichilia catigua, 42 but this is the rst report of this biomarker as the main polyphenol in Swietenia macrophylla. The major marker ion of m/z 451, which is unique in the BM extracts, could be attributed to cinchonain IA/IB.…”
Section: Ft-icr-ms Analysis With Molecular Formula Attributionsupporting
confidence: 53%
“…Note that the presence of phragmalintype limonoids in the BM extracts has been indicated by ESI(+)-MS analysis 27 and by other classical phytochemical approaches. Note that this molecule has also been reported in other types of tree woods such as Phyllocladus trichomanoides, 40 Rhizoma Smilacis glabrae 41 and Trichilia catigua, 42 but this is the rst report of this biomarker as the main polyphenol in Swietenia macrophylla. The major marker ion of m/z 451, which is unique in the BM extracts, could be attributed to cinchonain IA/IB.…”
Section: Ft-icr-ms Analysis With Molecular Formula Attributionsupporting
confidence: 53%
“…M a n u s c r i p t 35 identified in tomatoes (Vallverdu-Queral et al, 2010), in traditional Chinese medicines (Chen et al, 2014; and in wine where two oleanane-type triterpenoids substituted with galloyl and glucosyl moieties were identified, one of which exhibited sweet properties (Marchal et al, 2011).…”
Section: Structural Identification Of New Compoundsmentioning
confidence: 98%
“…developed a fast and reliable method based on detection using LTQ-Orbitrap MS for the identification of bioactive constituents in Sarcandra glabra, which is a frequently used traditional Chinese medicine. The method was useful for structural characterisation of several organic acids, caffeoyl derivatives, flavonoids, coumarins and terpenoids within 5 ppm error for each molecular ion Chen et al (2014). used hybrid LTQ-Orbitrap MS for the detection of bioactive compounds in Rhizoma Smilacis glabrae, a traditional Chinese medicine.…”
mentioning
confidence: 99%
“…In recent years, the combination of Orbitrap technology with a linear ion trap, known as LTQ Orbitrap mass spectrometer were introduced, which could provide all the traditional MS and MS n scan functions using a linear IT and high mass accuracy measurements (errors within 5 ppm) [17]. Our previous study indicated that this analytical technique has the potential capability of simple, sensitive and reliable detection and identification of complex samples such as TCMs [9].…”
Section: Introductionmentioning
confidence: 99%
“…When combined, the seven drugs have great therapeutic effects. Although the chemical constituents of the individual herbs have previously been well studied [7][8][9][10][11][12][13][14][15], little is known about the integrated chemical composition of PSORI-CM01. Unlike chemical drugs, botanical products contain a complex mixture of compounds.…”
Section: Introductionmentioning
confidence: 99%